The Role of Servant Leadership, Work Discipline, and Job Satisfaction on Teacher Performance in High Schools - Siswanto, Edy (International Journal of Social and Management Studies, 2020)
This study was conducted with the aim of knowing the effect of servant leadership, work discipline, and job satisfaction on teacher performance in high school. This study uses a quantitative approach with the number of research subjects as many as 124 respondents. The data processing method used path analysis and descriptive statistical methods. From the research results, it can be concluded that (1) servant leadership has no effect on job satisfaction, (2) work discipline has a positive effect on job satisfaction, (3) servant leadership has a positive effect on teacher performance, (4) work discipline has a positive effect on teacher performance, and (5) job satisfaction has no effect on teacher performance.